Diagnostic and Treatment Trends in Children With Kawasaki Disease in the United States, 2006–2015. Issue 10 (October 2019) - Dominguez, Samuel R.; Birkholz, Meghan; Anderson, Marsha S.; Heizer, Heather; Jone, Pei-Ni; Glode, Mary P.; Todd, James K.
Abstract : Objective: To evaluate variations in treatment practice and compliance with national guidelines for the diagnostic evaluation of children with Kawasaki disease (KD). Study Design: We used the Pediatric Hospital Information System database to analyze demographic, laboratory and treatment data from patients admitted with KD between January 1, 2006, and December 31, 2015. Results: During the study period, 12, 089 children with KD were diagnosed. Nearly all patients had a complete blood cell count, erythrocyte sedimentation rate, and C-reactive protein ordered. Fewer patients had alanine aminotransferase (48.6%) or a urinalysis (75.3%). A small percentage of children had abdominal imaging (11.5%), neck imaging (5.9%), and lumbar punctures (4.5%), and 36.0% of patients received antibiotic therapy. Obtaining echocardiograms pretreatment and the use of steroids and infliximab significantly increased over the study period ( P < 0.001). For patients who failed initial intravenous immunoglobulin (IVIG) monotherapy, 82.0% received a second dose of IVIG, 7.7% received steroids, 6.5% received infliximab, and 3.9% received combination therapy. Patients receiving infliximab or steroids as second therapy had a higher response rate than those who received only a second IVIG dose (87.9% versus 83.0% versus 73.3%, P < 0.001). Conclusions: KD remains a challenging diagnosis. Opportunities exist for earlier use of echocardiograms in the evaluation of children with potential KD. Significant variations in practice exist surrounding second-line therapy. Our data suggest superiority of second-line therapy use of infliximab or steroids over IVIG in terms of reducing need for additional therapies. Prospective, controlled studies are needed to confirm this finding.